Evaluasi Kualitas Web Portal STT Dharma Iswara Madiun Menggunakan Metode McCall - Andria Andria; Kusrini Kusrini; Armadyah Amborowati (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
This research aimed to evaluate web portal STT Dharma Iswara Madiun using McCall with a discussion of the quality factor is included in product operations consisting of five factors of quality of correctness, reliability, efficiency, integrity, and usability as well as analysis of data using the formula of quality factors and metrics and use some help tools. This study uses research instruments in the form of questionnaires and some application tools. The results showed how good the quality of the web portal STT Dharma Iswara Madiun, and any proposals that may be submitted to the portal web developers to develop more qualified web portal. Keywords—Quality Evaluation, Web Portal, McCall